2014
DOI: 10.1039/c4ce01041h
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Cd3P2 quantum dots emitting from the visible to the near infrared for bio-labelling applications

Abstract: Quantum dot composites (PS@Cd3P2, SiO2@Cd3P2) were prepared and employed for the first time as fluorescent probes for biological imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…77 The photoluminescence wavelength of Cd 3 P 2 quantum dots synthesized by Miao can span the visible to near-infrared spectral region, which is conducive to expanding the application of biological fluorescent labeling. 78…”
Section: Ctmentioning
confidence: 99%
“…77 The photoluminescence wavelength of Cd 3 P 2 quantum dots synthesized by Miao can span the visible to near-infrared spectral region, which is conducive to expanding the application of biological fluorescent labeling. 78…”
Section: Ctmentioning
confidence: 99%
“…Similarly, Miao et al synthesized Cd 3 P 2 QDs by the liquid phase method, which exhibited photoluminescent wavelengths spanning across the visible red light to the NIR spectral region. [10] The coating of PS and SiO 2 could enhance the optical and chemical stability of Cd 3 P 2 QDs, which is conducive to further biolabeling applications. In addition to ultrasmall InP and Cd 3 P 2 QDs, hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) doped with lanthanide ions, such as Eu 3+ , Tb 3+ , Gd 3+ , La 3+ , and Ce 3+ , have also been prepared for biolabeling.…”
Section: Metal-p Nms For Fimentioning
confidence: 99%
“…[ 19 ] The excellent optical, magnetic, and catalytic properties make Metal‐P NMs can be used as multifunctional diagnostic (photoacoustic imaging (PAI), fluorescent imaging (FI), magnetic resonance imaging (MRI), and nuclear imaging) and therapeutic (photothermal therapy (PTT), chemodynamic therapy (CDT), photodynamic therapy (PDT), and immunotherapy) agents for tumor theranostics. [ 5–19 ] Moreover, Metal‐P NMs are also suitable to be nanocarriers for delivering drugs owing to their degradable properties. [ 12 ] As a good medicine carrier, Metal‐P NMs can be loaded on chemotherapy drugs, photosensitizers, sonosensitizers, Fenton agents, genes, proteins, and various imaging contrast agents to achieve the integration of multimodal imaging and therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the shell was thin (0.3 nm), leading to batch dependent air stability. Ding et al [31] reported the encapsulation of Cd 3 P 2 NCs within silica nanobeads and polystyrene microspheres. Multiple QDs are contained within the microspheres making their practicality problematic [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [31] reported the encapsulation of Cd 3 P 2 NCs within silica nanobeads and polystyrene microspheres. Multiple QDs are contained within the microspheres making their practicality problematic [31]. These strategies having their limits, moving forward there is a great opportunity to study shelling methods for II-V semiconductor nanocrystals.…”
Section: Introductionmentioning
confidence: 99%